A circulação de sentidos em “eu não mereço ser estuprada”: uma leitura do acontecimento midiatizado - Dias, Marlon Santa Maria (2016)
The present study investigates emergent forms of social mobilization generated on digital environments and their eventful character. The intensification of the society mediatization process points to the interpenetration between social fields, whose functioning is crossed by logics of a media culture (FAUSTO NETO, 2008), besides reconfiguring the dynamic and social practices and establishing a new ambience, that is, a new form of presence of the subject upon the world (SODRÉ, 2002). The events in a society in mediatization process also modify and find on digital environments new spaces for their development and their discursive constitution. Such events have their existence linked to the digital nature of the platforms in which they emerge. Moving from the conceptual approach that considers the transformations of society facing the midiatization process and understanding that the events are also modified by this context, we aim at understanding, describing and analyzing how such mediatized events are built. For such, our empirical object is the discursive production concerning the mobilization Eu não mereço ser estuprada (ENMSE; “I don’t deserve to be raped”), which rises from an anti-raping protest articulated, above all, by actors on digital social networks. Such actors, by means of distinct and singular discursive strategies, invest on interactions aiming at making their actions visible, connecting with those who share the same digital space and producing their own interpretations about the event. The methodology adopted by the present research develops as a case study with mediatic-communicational approach (BRAGA, 2008; FORD, 1998), in which we utilize online mapping techniques and non-participatory covert observation (JOHNSON, 2010) for collecting data. To read this material, we draw inspiration from the semiological analysis proposed by Verón (2005), Pinto (2002) and Peruzzolo (2004). At its ending, the study allowed the identification of five factors that cross the mediatized event by means of distinct logics: the scientific system, the mediatic system, the actor Nana Queiroz, the networks and the social actors. Each of these spheres produces logics that promote the discursive production that constitutes ENMSE. The case analysis signals that it is impossible to mark a point that concentrates the authoring of the event. The intelligibility reference of the event ceases to belong to already legitimized social fields and starts being dynamized by technodiscursive procedurals that open to different streams, shifting the leading role of the action from a single instance. For circulating in a mediatized ambience, the event constitutes by means of fragments and discontinuities, coupling logics of diverse systems, which affect and generate derivations, with meanings that escape the traditional discursive mediatic circulation.